Antigen specific T-cell responses against tumor antigens are controlled by regulatory T cells in patients with prostate cancer - Hadaschik, Boris; Su, Yun; Hüter, Eva; Ge, Yingzi; Hohenfellner, Markus; Beckhove, Philipp (The journal of urology, 2012)
Purpose - Immunotherapy is a promising approach in an effort to control castration resistant prostate cancer. We characterized tumor antigen reactive T cells in patients with prostate cancer and analyzed the suppression of antitumor responses by regulatory T cells. - Materials and Methods - Peripheral blood samples were collected from 57 patients with histologically confirmed prostate cancer, 8 patients with benign prostatic hyperplasia and 16 healthy donors. Peripheral blood mononuclear cells were isolated and antigen specific interferon-γ secretion of isolated T cells was analyzed by enzyme-linked immunospot assay. T cells were functionally characterized and T-cell responses before and after regulatory T-cell depletion were compared. As test tumor antigens, a panel of 11 long synthetic peptides derived from a total of 8 tumor antigens was used, including prostate specific antigen and prostatic acid phosphatase. - Results - In patients with prostate cancer we noted a 74.5% effector T-cell response rate compared with only 25% in patients with benign prostatic hyperplasia and 31% in healthy donors. In most patients 2 or 3 tumor antigens were recognized. Comparing various disease stages there was a clear increase in the immune response against prostate specific antigens from intermediate to high risk tumors and castration resistant disease. Regulatory T-cell depletion led to a significant boost in effector T-cell responses against prostate specific antigen and prostatic acid phosphatase. - Conclusions - Tumor specific effector T cells were detected in most patients with prostate cancer, especially those with castration resistant prostate cancer. Since effector T-cell responses against prostate specific antigens strongly increased after regulatory T-cell depletion, our results indicate that immunotherapy efficacy could be enhanced by decreasing regulatory T cells.